A prática da gestão democrática em escolas públicas: um estudo comparativo entre uma escola pública militarizada e outra não militarizada de uma capital do nordeste - Lacerda, Silvana Márcia Batista de (2018)
This research presents an analysis of the democratic management practices in public schools, through a comparative study between a militarised public school and a non-militarised public school of a capital from Brazil's northeast. In order to carry out the research, it was used a qualitative approach. The data were collected through interviews, known as informal conversations, with a semi-structured script, the shadowing technique, a kind of nonparticipant observation, and also a document analysis. For the purpose of analyzing the work, it was used the Studies Based on Practice (SBP). As a result, it can be affirmed that, despite the fact that in both educational institutions surveyed, although democratic practices was not seen, there are just signs of democracy in some situations, that is why them could not be characterized as having a completely democratic management. Moreover, it also showed that the greatest obstacle in defining them as practitioners of democratic management in its fullness was the lack of participation of those whose constitute the school community, which led us to conclude that having a School Council is not enough to have, in fact, a participation which generates democratization and decentralization of power. In addition, the lack of participation constitutes a problem which comes from a culture rooted in a society in need of awareness, whom result is a cultural transformation. To sum up, through these results it could be understood that it is not the military or non-military nomenclature that can set up a democratic management, but the practices of that management in their reality.